Welfare Economics and the Theory of Second Best - Davis, Otto A.; Whinston, Andrew B. (Review of Economic Studies, 1965)
Journal Article Welfare Economics and the Theory of Second Best Get access Otto A. Davis, Otto A. Davis Carnegie Institute of Technology Search for other works by this author on: Oxford Academic Google Scholar Andrew B. Whinston Andrew B. Whinston University of Virginia Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 32, Issue 1, January 1965, Pages 1–14, https://doi.org/10.2307/2296327 Published: 01 January 1965